ETIKA JURNALISTIK DALAM PENGEMBANGAN DAKWAH (EJDPD) - Kasman, Suf (Jurnal Dakwah Tabligh, 2018)
Journalistic Ethics in Development of Da'wah is one of the most crucial used communication media between individuals and organizations across the world today, as a medium of sharing and disseminating information Islam. The advantages offered by Journalistic Ethics in Development of Da'wahis very effectively to convey the message of dakwah. Indeed, dakwah is one of the successful activities implemented through social media whenever the renowned da’ie also uses this method. Therefore, this paper reveals the role of social media (Journalistic) in disseminating the message of dakwah to the community. It focuses on the social media factors which affect publicizing Islamic information. Various aspects such as the effectiveness of the messages, the role of the da’ie, the medium used, the right approach, and the concept of amar ma’ruf nahi munkar are also peeled. This paper also discusses the need for social media to be used by the community in order to get more exposure toward Islamic messages. In fact, all parties should have the awareness on the importance of social media as a medium of communication for dakwah in this era of information. Journalistic Ethics is the subdivision of applied ethics dealing with the specific ethical principles and standards of media, including broadcast media, film, theatre, the arts, print media and the internet. Ethical standard refers to standard principles that encourage the greater values of trust, fairness and benevolence. Ethical standards may refer to responsibilities for some professionals. Generally, the objective of the study is to know Journalistic Ethics in Development of Da'wah. The findings of this study will provide useful information about Journalistic Ethics in Development of Da'wah, that The researchers can conclude that Journalistic Ethics in Development of Da'wah have their own strength but are very keen in spreading da’wah and have their own strong fan base of followers in social media. Therefore, a preliminary conclusion can be made that social media, especially journalistic can be used as a platform for da’ies to spread da’wah and well-meaning messages.